Severe Fetal Distress and Umbilical Cord Strangulation - Giovanni Larciprete; Carlotta Montagnoli; Paolo Fusco (Case Reports in Medicine)
We describe an extreme case of amniotic band syndrome, presented with fetal stress during labor and associated with strangulation of umbilical cord.